Can someone please help me with this one

Hint: separate the fractions; \frac{(4 - 3)}{6} = \frac{4}{6} - \frac{3}{6} as an example

1 Like

if xy \neq0 that means that either of those value can’t be 0 because 0(x=0) time y = 0 and x times 0(y=0) = 0 and 0(x=0) times 0(y=0) =0

Now, \dfrac{x-1}{xy} can be written like \dfrac{x}{xy}-\dfrac{1}{xy}

Thus, we can further simplify it to \dfrac{\cancel{x}}{\cancel{x}y}-\dfrac{1}{xy} = \dfrac{1}{y}-\dfrac{1}{xy}

2 Likes

thanks guys/girls, i made a mistake when cancelling out the two x’es… I forgot that it turns into a 1 maybe i should work slower cause your solutions are not new theory to me so i guess i’m working too sloppy

thanks for ur patience